Statin Use and Influenza Vaccine Effectiveness in Persons > 65 Years of Age, Taiwan - Tsai, Lung-Wen; Chen, Yung-Tai; Shih, Chia-Jen; Ou, Shuo-Ming; Chao, Pei-Wen; Lo, Shih-Hsiu (Emerging infectious diseases, 2020)
Debates on whether statin use reduces the effectiveness of influenza vaccines against critical illness and death among persons >65 years of age continue. We conducted a study of 9,427,392 persons >65 years of age who did and did not receive influenza vaccinations during 12 consecutive influenza seasons, 2000-01 through 2011-12. Using data from Taiwan's National Health Insurance Research Database, we performed propensity score-matching to compare vaccinated persons with unvaccinated controls. After propensity score-matching, the vaccinated group had lower risks for in-hospital death from influenza and pneumonia and for hospitalization for pneumonia and influenza, circulatory conditions, and critical illnesses compared with the unvaccinated group. We stratified the 2 groups by statin use and analyzed data by interaction analysis and saw no statistically significant difference. We found that influenza vaccine effectively reduced risks for hospitalization and death in persons >65 years of age, regardless of statin use.